Something is Working—But Why? Mixed Rooms in the Norwegian Army. Issue 3 (2nd July 2016) - Ellingsen, Dag; Lilleaas, Ulla-Britt; Kimmel, Michael
Abstract: In a qualitative study of masculinities in the Norwegian Armed Forces, we found the expected sexual harassment and some more unexpected episodes of what we name solidarity masculinity. But we also uncovered some possible and surprisingly positive effects of male and female conscripts living together in so-called mixed rooms. The rooms seemed to function in a way that promoted mutual understanding, de-sexualization and reduced sexual harassment. Our findings gained a lot of attention in the media worldwide, and they have also been tested empirically by other Norwegian researchers using quantitative methods. Although their findings strengthen our hypothesis that "something is working" inside these mixed rooms, we are doubtful about the validity of some of their findings and how they interpret them. We doubt that what is experienced by putting young women and men in the same room for 7–8 weeks can tell us much about the possibilities of breaking through the glass ceiling for women in male-dominated organizations, or speaks in favour of higher quotas for women in male bastions. The effects of these rooms might best be understood as a kind of gender-positive secondary socialization in cultures where gender equality enjoys a high standing. Strong leadership, common goals, and equal positions also seem to be needed in order to get the desired effect of reduced stereotypes. This finding is in line with the contact hypothesis postulated by Thomas Pettigrew in his studies of integration. To our knowledge, our study is the first on mixed rooms in the Armed Forces, despite the fact that they have been in use in Scandinavia for almost 25 years.